2020
DOI: 10.3390/metabo10080325
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolomic Analysis of Dendrobium officinale under Different Cultivation Substrates

Abstract: Dendrobium officinale, a precious herbal medicine, has been used for a long time in Chinese history. The metabolites of D. officinale, regarded as its effective components to fight diseases, are significantly affected by cultivation substrates. In this study, ultra-performance liquid chromatography mass spectrometry (UPLC-MS/MS) was conducted to analyze D. officinale stems cultured in three different substrates: pine bark (PB), coconut coir (CC), and a pine bark: coconut coir 1:1 mix (PC). A total of 529 metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…Untargeted metabolic analysis has been widely used for a comprehensive comparison of detailed metabolite identi cations under different conditions [11,22,23] . In our study, a total of 272 metabolites were detected in the current study, and the number of detections was greater than some studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Untargeted metabolic analysis has been widely used for a comprehensive comparison of detailed metabolite identi cations under different conditions [11,22,23] . In our study, a total of 272 metabolites were detected in the current study, and the number of detections was greater than some studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a work aimed to compare metabolite characteristics between two medicinal Dendrobium found 139 major metabolites from D. o cinale [20] . Others found more metabolites after different treatments, for example, one study shows a total number of 529 metabolites based on different cultivation substrates [23] , another found 3,655 annotated metabolites with Ultraviolet-B radiation treatments, indicating that ultraviolet-B radiation helps to the accumulation of active compounds in D. o cinale. Although different studies showed signi cant differences in the number of metabolites detected, this suggests that environmental factors play an important role in the types and amounts of metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…This research characterizes the biosynthetic pathways of active compounds in D. officinale , which provides an important basis for its uses as a medicinal material ( Table 1 ; Yuan et al, 2020a ). Transcriptomic analysis was also used to investigate the effects of various factors on the accumulation of active compounds, including the material location, hormones and more ( Chen et al, 2019 ; Ren et al, 2020 ; Zuo et al, 2020 ). Moreover, the potential molecular mechanisms of a variety of physiological processes were analyzed, such as response to stress, flowering and symbiotic relationships ( Wang et al, 2018 ; Zou et al, 2018 ; Li H. et al, 2021 ).…”
Section: Transcriptomic Research In Dendrobium Officinalementioning
confidence: 99%
“…Bibenzyls (belonging to phenolic compounds) including erianin and gigantol are mainly detected in roots and stems ( Adejobi et al, 2021 ). Moreover, increasing evidence shows that the biosynthesis and accumulation of diverse active compounds are often influenced by various environmental factors such as different cultivation substrates ( Zuo et al, 2020 ) and habitats ( Lei et al, 2018 ). Therefore, it is important to dissect the physiological and molecular mechanisms underlying accumulation of those active compounds during the growth and development of different tissues for breeding by genetic improvement, cultivation and management practices in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…The VIP value determined significantly regulated metabolites between groups ≥ 1, fold change ≥ 1 (17). VIP values were extracted from OPLS-DA results, containing score plots and permutation plots generated using R package MetaboAnalystR.…”
Section: Metabolite Identification and Kegg Pathway Analysismentioning
confidence: 99%